A study on green innovation and entrepreneurship in the dual carbon era and its implications for the energy market - Jingjing Sun; Xin Guan; Zeyu Wang; Jiali Zhang; Yepei Tan; Peng Nie (Scientific Reports)
Abstract The term “dual-carbon goals” refers to the commitment of nations or regions to achieving carbon peaking and carbon neutrality. In this context, this study specifically denotes reducing carbon emissions and promoting the transformation and upgrading of energy markets through green innovation and entrepreneurial activities. This study explores the dynamic relationships among key variables in the energy market. It focuses on the impact of investments in green technological innovation on the balance of energy supply and demand, as well as market demand. The findings aim to provide scientific evidence to support the achievement of sustainable development goals. Through system dynamics modeling, this study analyzes the intricate relationships among energy demand, supply, green technology innovation investment, and market demand. In the realm of complex network analysis, market participants are categorized into conservative, moderate, and innovative groups, and their market behavior patterns are examined. In the data mining and machine learning phases, this study constructed a predictive model with an accuracy rate of 85%, forecasting the impact of future green innovation and entrepreneurship on market demand and energy supply. The results indicate that, in the dual-carbon era, investment in green innovation and entrepreneurship plays a significant role. This study enhances the proportion of renewable energy in the market, reduces carbon emissions, and accelerates the transformation of energy demand. Conservative market participants dominate the energy market, but the rise of innovative market participants suggests a positive influence of green innovation and entrepreneurship on market structure. The accuracy of the predictive model provides a reliable basis for policy formulation and strategic planning, offering scientific guidance for achieving sustainable energy development goals.